The Use of Hydroxyapatite Loaded with Doxycycline (HADOX) in Dentoalveolar Surgery as a Risk-Reduction Therapeutic Protocol in Subjects Treated with Different Bisphosphonate Dosages - Sacco, Roberto; Sartoretto, Suelen Cristina; de Brito Resende, Rodrigo Figueiredo; de Albuquerque Calasans-Maia, Jose; Rossi, Alexandre Malta; de Souza Lima, Victor Hugo; de Almeida Barros Mourão, Carlos Fernando; Granjeiro, Jose Mauro; Yates, Julian; Calasans-Maia, Monica Diuana (Medicina (Kaunas, Lithuania), 2022)
Medication-related osteonecrosis of the jaw (MRONJ) is considered as a severe adverse side effect of specific drugs such as anti-resorptive and anti-angiogenic medications. Evidence suggests that MRONJ is linked to invasive dental procedures, mainly dentoalveolar surgery. Several preventive strategies to minimize the risk of developing MRONJ have been investigated. However, no investigation has been attempted to evaluate the therapeutic effect of local drug-delivery technology as a preventive strategy protocol. The aim of this study is to evaluate the efficacy of hydroxyapatite-containing doxycycline (HADOX) in rats with high-risk MRONJ development. All the rats used in this study were divided into seven groups. Six groups of rats out of seven were exposed to two different doses of antiresorptive drug therapy for four weeks before undergoing an upper incisor extraction. After 28 days, all the animals were euthanized, and the bone blocks were processed for histological and histomorphometrical evaluation. The histomorphometric analysis confirmed that newly formed bone (NFB) was present in all groups, with significant differences. NFB in the HADOX group treated with zoledronic acid at 4% showed (28.38; C.I. 22.29–34.48), which represents a significant increase compared to HA (15.69; C.I. 4.89–26.48) (p = 0.02). A similar pattern was observed in the HADOX group treated with zoledronic acid 8% ZA treatment (p = 0.001). Conclusions: HADOX did not inhibit any bone repair and reduced early inflammatory response. Hence, HADOX could promote bone healing in patients undergoing antiresorptive drug therapy.